Sources of funding and sustainability of Microfinance institutions in Cameroon: an explanation using the pecking order theory - KEMDONG TENEKEU Nicodème (Revue Internationale des Sciences de Gestion, 2022)
The purpose of this analysis is double. Firstly to Identify sources of funding using hierarchical funding theory and secondly analyzed their impact on the sustainability of Cameroonian MFIs. To achieve this we used panel data on a sample of 62 MFIs whose age varies between 9 years over the period 2009-2015. Our results show us that equity is the primary source of financing for MFIs, followed by grants, debt and deposits from clients (members). Furthermore, MFIs belonging to the first category use members’ own funds, debts and deposits as their main funding resources, while the second category use equity and grants. In addition, MFIs located in the French areas only use equity as their main financing resources, while those located in the Anglophone areas use equity and grants. Our results also show us that equity has a positive and significant influence on the sustainability (OSS and FSS), while grants has a negatively significant the sustainability of MFI. Debt is negative and positively significant on the sustainability of MFIs.